Kedudukan Hukum Pengelolaan Bersama Dana Tanggung Jawab Sosial dan Lingkungan Perusahaan - Kurdi Kurdi; Purnama Trisnamansyah (Asas Wa Tandhim: Jurnal Hukum, Pendidikan Dan Sosial Keagamaan, 2027)
Article 9 of West Aceh Regency Qanun No. 10 of 2015 states that Corporate Social and Environmental Responsibility Fund or TJSLP are managed entirely by the company in accordance with a mutual agreement with the regency government. However, in practice, there has been discussion of joint management through a joint account. The results of this normative juridical research show the phrase “managed entirely by the company” grammatically precludes the possibility of external intervention, including by the local government. Meanwhile, the phrase “in accordance with an agreement” gives rise to interpretive ambiguity. From a hierarchical perspective, the joint management mechanism has the potential to conflict with Government Regulation No. 47 of 2012, which classifies TJSLP funds as corporate expenses, and Law No. 40 of 2007, which affirms that management responsibility lies with the company’s governing body. It is concluded that joint management does not yet have a strong legal basis and requires the establishment of clearer legal norms.